IMPACT OF THE ADVANCE INCOME TAX APPLICATION - Gutiérrez Jaramillo, Néstor Daniel (2015)
The minimum advance income tax in the Republic of Ecuador is one of the tax burdens that generates more controversy among taxpayers, due to its heterodox nature that levies taxes based on calculations of capital, assets, costs, expenses and income unrelated to the income determined for the fiscal year itself. This tax burden is part of a measure to combat low collection of direct taxes caused by tax evasion, which directly affects the income tax. For the development of the research the basic information was requested from the Internal Revenue Service and the databases avai-lable on the webpage of this public institution, which were processed statistically. We also applied surveys allowing us to know the perception of corporate taxpayers in the province of El Oro. As a result it was established that for the period 2006-2012 tax reforms contributed to the increase of the tax burden and collection of Direct and Indirect Taxes by the Gover-nment in the Province of El Oro, helping to strengthen the progressivity of the tax collection system.